On wings of diesel: trucks, identity and culture in Pakistan - Elias, Jamal J (India: One world publication, 2011)
Beginnings -- History of a dystopic utopia -- Education and boundaries of class -- Trucks and transportation -- Trucks, truckers, and society -- Truck design and an artisanal trade -- Structure, motif, and meaning -- Religion, identity, and trucks -- Meaning, modernity, and shifting signifiers -- Truck design, art, and agency -- Appendix : Truck verse.
Include bibliographic references and index
Keywords: Folk art $z Pakistan $x Themes, motives